INTERNALISASI KARAKTER MANDIRI SISWA MELALUI EKTRAKULIKULER MEMANAH DI SD DAARUL QURAN INTERNASIONAL - Salwa; Miftachudin; Muttaqin, Muhammad Fauzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to evaluate the influence of archery extracurriculars on internalizing independent character values ​​in Daarul Quran International Elementary School students. The research method used is qualitative research with a descriptive approach. The research subjects consisted of extracurricular teachers, coaches and students who took part in archery extracurricular activities at the school. Data collection techniques include observation, interviews and documentation. Data validation was carried out through triangulation of sources and methods. Data analysis was carried out using data reduction, data presentation, and concluding. The results of the research show that the archery extracurricular at Daarul Quran International Elementary School has a positive impact on internalizing students' independent character. Students who take part in this activity show an increase in independence, discipline, decision-making ability, and sports ethics. Therefore, it is recommended that schools continue to support and develop extracurricular activities such as archery as part of efforts to build student character.